OPPORTUNITIES AND CHALLENGES OF ARTIFICIAL INTELLIGENCE ADOPTION IN DEMOCRATIZATION AND PUBLIC POLICY: A CASE STUDY OF THE TANGERANG LIVE APPLICATION - Fuad, Anis; Dewi, Shanty Kartika; Djuyandi, Yusa (Universitas Padjadjaran, 2025)
This study examines the role of the Tangerang LIVE application in promoting democratization and public policy through digital innovation. The approach used is exploratory qualitative, with literature studies, document analysis, and non-participatory observation of citizen interactions—including user reviews, agency responses, and bold media—from May 2024 to March 2025. Data were analyzed using thematic techniques assisted by NVivo, with validation through source triangulation. The focus of the study encompasses (1) citizen accessibility and participation (e-participation), (2) government transparency and accountability, and (3) digital democracy practices, including evidence-based policy deliberations. The results show that the LAKSA feature in Tangerang LIVE provides a space for citizens to convey their aspirations and complaints, most of which are responded to quickly and transparently by the government. This reflects the application of e-governance principles. However, technical constraints, such as application bugs and login difficulties, remain obstacles. Within the UTAUT theoretical framework, digital citizen participation is greatly influenced by perceptions of the ease and benefits of technology. Complaint data also has the potential to be analyzed with artificial intelligence (AI) to strengthen evidence-based policy research. The study concludes that Tangerang LIVE is a real-life example of digital innovation that promotes inclusive, participatory, and responsive governance. AI integration and technical system enhancements are needed to strengthen digital democracy at the local level.